Baculovirus penaei as a risk factor for bacterial infections in the hepatopancreas of Penaeus vannamei - Varela-Mejías, Alexander (2019)
The incidence of bacterial infections in shrimp hepatopancreas cultivated in the Gulf of Nicoya, Costa Rica, presented a high impact on yields in 2016-2017, affecting the survival of the animals and shrimp farm production. In addition, important incidences of Baculovirus penaei, detected in post-larvae used in part of the shrimp ponds, were reported. An Odds Ratio analysis was performed in an observational case-control study to determine the possible participation of this virus as a risk factor for subsequent bacterioses. The study demonstrates the active participation of Baculovirus penaei as an important risk factor. Survival data are presented by ponds infected by the virus vs free ponds.